PENGUASAAN NEGARA TERHADAP SUMBER DAYA DALAM PANDANGAN ISLAM - Ibrohim, Muhammad; Athoillah, Muhammad (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2023)
The Right to Control the State (HMN) as stated in Article 33 of the 1945 Constitution is the juridical basis that regulates state power over natural and artificial resources. Through this research, the author describes the views of Salaf Islamic boarding school literature on the use of state resources and HMN to explore their conformity with Islamic teachings. This research method uses library research with a deductive approach. As a result of this research, the author concluded that in the view of Salaf Islamic boarding school literature, state resources are a blessing from Allah SWT. give it to all the people. This favor must be used to realize the common good and must not be monopolized. In the view of Salaf Islamic boarding school literature, HMN is also considered a manifestation of the government's obligation to manage state resources to create benefits for all people. Based on this conclusion, the assumption that HMN violates Islamic teachings is incorrect. However, the government must always strive for the benefit of managing state resources, including delegating its power to the private sector.